Survival of a young male patient with catastrophic acute left main coronary artery occlusion and cardiogenic shock - Lagaputi Rama Rao; Silpa Chowdari Nallapaneni; Naga Sri Haritha Parvathaneni; Akif Ahamad Baig; Bikash Sahu (Heart India)
Total occlusion of the left main coronary artery (LMCA) is a rare but highly lethal event in acute coronary syndrome. It can lead to extensive myocardial infarction and hemodynamic instability. Despite advancements in percutaneous coronary intervention (PCI), mortality remains high. A 35-year-old male presented with chest pain, dyspnea, and hemodynamic instability. Diagnostic workup revealed LMCA thrombotic occlusion with extensive myocardial involvement and cardiogenic shock (CS). Prompt intervention, including thrombus aspiration, angioplasty, and hemodynamic support with intra-aortic balloon pump and venoarterial extracorporeal membrane oxygenation, was initiated. The patient’s condition gradually improved with comprehensive management, including pharmacotherapy and intensive care support. LMCA occlusion presents challenges due to its extensive myocardial distribution and high mortality rates, particularly when complicated by CS. PCI combined with circulatory support is crucial for restoring perfusion and improving outcomes. Achieving optimal flow and providing postprocedural care significantly impact patient prognosis. Rapid diagnosis and intervention are critical in LMCA occlusion with CS. A multidisciplinary approach incorporating advanced circulatory support and timely revascularization are the keys in improving patient outcomes. Comprehensive postprocedural care is essential for ensuring successful recovery and survival.